2022
DOI: 10.36347/sajp.2022.v11i01.002
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry and Pharmacological Activities of Swietenia macrophylla King (Meliaceae)

Abstract: Mahogany is a Meliaceae family exotic plant that includes three species: Swietenia macrophylla king, S mahogany L. Jacq., and S. humulis Zucc. This genus is predominantly found in the humid zone of the New World and the Amazon region of South America. The purpose of this review article is to look at its taxonomical classification, vernacular names, pharmacological activities and its phytochemistry. Scientific studies have found that the crude extract from S. macrophylla seeds has antibacterial, anti-malaria, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…8 Phenols and flavonoids have been widely reported to have antioxidant activity in both in vivo and in vitro studies. 5 The results of a systematic review show that the phytochemical content of S. macrophylla seeds is mostly tannins, alkaloids, saponins, terpenoids, and stigmasterol. 10 A study on the determination of the phytochemical content of S. macrophylla seeds revealed a high concentration of phenolics (46.22 mg), flavonoids (26.12 mg), and tannins (9.23 mg).…”
Section: Resultsmentioning
confidence: 99%
“…8 Phenols and flavonoids have been widely reported to have antioxidant activity in both in vivo and in vitro studies. 5 The results of a systematic review show that the phytochemical content of S. macrophylla seeds is mostly tannins, alkaloids, saponins, terpenoids, and stigmasterol. 10 A study on the determination of the phytochemical content of S. macrophylla seeds revealed a high concentration of phenolics (46.22 mg), flavonoids (26.12 mg), and tannins (9.23 mg).…”
Section: Resultsmentioning
confidence: 99%
“…There are similarities in the phytochemistry of these two Swietenia species. Phytochemical studies have revealed that the primary bioactive compounds in Swietenia seeds are limonoids, specifically swietenine and its derivatives [14,20,30,47]. Limonoids are triterpene derivatives that have lost of four carbon atoms, so the side chain becomes a furan ring [30].…”
Section: Phytochemistry Of Swietenia Seeds With Antidiabetic Activitymentioning
confidence: 99%
“…One such potential source is broadleaf mahogany (Swietenia macrophylla), abundantly found in Indonesia. Its seeds contain a plethora of compounds including limonoids, fatty acids, and steroids (Telrandhe et al, 2022). Traditionally, mahogany seeds have been utilized in treating conditions such as high blood pressure, diabetes, and infections.…”
Section: Introductionmentioning
confidence: 99%